Peran Struktur Organisasi Dalam Efektivitas Koordinasi Dan Pengambilan Keputusan Di Perusahaan Manufaktur - Riri Nurmaya (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Manufacturing companies face challenges in maintaining operational efficiency amid high productivity demands. Organizational structure is an important foundation in the management of a manufacturing company to ensure operational efficiency and the achievement of business objectives. In manufacturing companies, organizational structures are generally hierarchical and functional, dividing tasks and responsibilities based on departments such as production, quality control, marketing, finance, human resources, and research and development. This research aims to examine the role and effectiveness of organizational structure in supporting performance in a manufacturing company. With a descriptive-qualitative approach, an analysis is carried out on the relationship between work units, communication flows, and how the decision-making mechanism is made. The results of the study show that a clear and clearly defined organizational structure is able to improve coordination, speed up decision-making, and minimize duplication of work. Therefore, designing an appropriate and efficient organizational structure is a strategic factor in increasing the competitiveness of manufacturing companies in the midst of increasingly fierce industrial competition.